Analisis Gugatan Cerai Istri kepada Suami menurut Undang–Undang No. 16 Tahun 2019: Studi Kasus Putusan Nomor 2455/Pdt.G/2018/Pa.Jt - Rikmadani, Rd. Yudi Anton; Suprobo, Teguh (Advokasi Hukum & Demokrasi (AHD), 2024)
Marriage is an important part of human life because it involves relationships between people. Law No. 16 of 2019 adheres to the principle that prospective spouses must be mature in both body and soul in order to carry out marriage to achieve the goal of marriage well without ending in divorce and to have good and healthy offspring. Therefore, there is a minimum age limit for marriage so that both partners are physically and mentally ready to move forward in marriage. Although the age limit is clearly regulated, in reality, many marriages occur below the minimum age. This leads to many divorce cases due to not being physically and mentally ready for married life.